2005
DOI: 10.1128/jb.187.12.4207-4213.2005
|View full text |Cite
|
Sign up to set email alerts
|

Defense against Protein Carbonylation by DnaK/DnaJ and Proteases of the Heat Shock Regulon

Abstract: Protein carbonylation is an irreversible oxidative modification that increases during organism aging and bacterial growth arrest. We analyzed whether the heat shock regulon has a role in defending Escherichia coli cells against this deleterious modification upon entry into stationary phase. Providing the cell with ectopically elevated levels of the heat shock transcription factor, sigma32, effectively reduced stasis-induced carbonylation. Separate overproduction of the major chaperone systems, DnaK/DnaJ and Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 31 publications
3
89
1
2
Order By: Relevance
“…Protein damage in the form of carbonylation and disulphide bond formation is known to accumulate in E. coli stationary-phase cultures (Dukan & Nystrom, 1998). Heat-shock proteins are induced during stationary phase in this organism via the rpoH-encoded alternative sigma factor (Jenkins et al, 1991), and the action of DnaK/DnaJ and GroEL/GroES has been shown to protect against such damage through stabilization of polypeptides and assisting in their folding (Fredriksson et al, 2005;Siegenthaler & Christen, 2005;Tang et al, 2006). Although C. jejuni lacks any homologue of rpoH, the stationary-phase induction of heat shock genes may represent a similar response to protein damage, albeit regulated by a different mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Protein damage in the form of carbonylation and disulphide bond formation is known to accumulate in E. coli stationary-phase cultures (Dukan & Nystrom, 1998). Heat-shock proteins are induced during stationary phase in this organism via the rpoH-encoded alternative sigma factor (Jenkins et al, 1991), and the action of DnaK/DnaJ and GroEL/GroES has been shown to protect against such damage through stabilization of polypeptides and assisting in their folding (Fredriksson et al, 2005;Siegenthaler & Christen, 2005;Tang et al, 2006). Although C. jejuni lacks any homologue of rpoH, the stationary-phase induction of heat shock genes may represent a similar response to protein damage, albeit regulated by a different mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…These extensions are probably structurally disordered when unbound to polynucleotides because they are disproportionately detected by proteome-wide predictions of regions of intrinsic structural disorder (45,46). Lon is known to target defective proteins (47)(48)(49)(50)(51), probably because its unfoldase can process proteins that contain intrinsically disordered a These peptidomic samples are described in the Fig. 4 legend.…”
Section: Discussionmentioning
confidence: 99%
“…4, dnaK (33,50,65) and hns (33,66), are known to be carbonylated in response to starvation, and it is possible that they are subsequently targeted for proteolysis. Although Lon is the major protease of aberrant proteins in bacteria (47)(48)(49)(50)(51), ClpABPX (49 -51, 67), HslUV (50), and HtrA (49, 68) also have important roles. Therefore, two modes of protein degradation are likely upregulated by phagocytosed Salmonella, PolyP/Lon-dependent directed proteolysis of ribosomal proteins and ClpABPX/HslUV/ HtrA/Lon proteolysis of defective stress response factors.…”
Section: Fig 4 Cluster Analysis Of the Lc-ms Datamentioning
confidence: 99%
“…Toutes les protéines ne sont pas égales face aux altérations provoquées par les espèces réactives d'oxygène (ROS) [3,4]. Dans la population humaine, les protéines vitales les plus susceptibles à l'oxydation représenteraient différents « maillons faibles », dont l'atteinte se manifeste au fur et à mesure que l'individu avance en âge.…”
Section: La Chimie De L'usure Et Les Mécanismes De La Résilienceunclassified
“…Une des causes du vieillissement cellulaire est l'usure de ces systèmes de réparation et de renouvellement moléculaires qui se répercute sur la qualité du protéome entier. Or, ces systèmes -et notamment les protéines chaperons qui constituent un système de protection plus que de réparation -sont composés de protéines vulnérables, sensibles aux altérations chimiques comme l'oxydation [3,4]. Un cercle vicieux s'installe alors : l'oxydation des chaperons entraîne le mauvais repliement des protéines, leur oxydation [3,5], et donc une synthèse inefficace ne faisant qu'accroître l'oxydation [5], etc.…”
Section: La Chimie De L'usure Et Les Mécanismes De La Résilienceunclassified